2012
DOI: 10.1016/j.biopsych.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Estradiol and Progesterone on Serotonergic Function

Abstract: Background Ovarian hormones may contribute to the vulnerability to depression as well as to the response to antidepressants (ADs). Previously we reported that acute systemic treatment with estradiol or progesterone blocked the ability of the selective serotonin reuptake inhibitor (SSRI), fluvoxamine, to inhibit serotonin transporter (SERT) function in ovariectomized (OVX) rats. In this study, behavioral consequences as well as receptor mechanisms underlying these hormonal effects were investigated. Methods U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 79 publications
5
36
0
2
Order By: Relevance
“…In our present study, estrogen (as EB or E2) and P were administered in combination. Consistent with our previous report (Benmansour et al 2012), acute administration of these hormones did not produce an antidepressant-like effect. Our group has previously reported using chronoamperometry to measure the rate of clearance of exogenous serotonin from the CA3 region of the hippocampus, that progesterone blocked the antidepressant-like effect of EB (Benmansour et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our present study, estrogen (as EB or E2) and P were administered in combination. Consistent with our previous report (Benmansour et al 2012), acute administration of these hormones did not produce an antidepressant-like effect. Our group has previously reported using chronoamperometry to measure the rate of clearance of exogenous serotonin from the CA3 region of the hippocampus, that progesterone blocked the antidepressant-like effect of EB (Benmansour et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, results of the acute study indicate a reduced efficacy of DMI in the FST in the presence of ovarian hormones. This phenomenon seems consistent with the diminished SSRI efficacy reported in a previous study from our group (Benmansour et al 2012) with an identical hormone administration paradigm. In that study, the effect of estrogen on SSRI function was found to be dependent on the ER subtype, with ERα mediating its inhibitory effect on the ability of an SSRI to inhibit the SERT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The slowing of the 5-HT clearance was due to activation of β-estrogen and/or GPR30. Meanwhile, the blockade of luvoxamine's inhibitory efect on 5-HT clearance was mediated by α-estrogen [42]. Both of them used diferent signaling mechanisms.…”
Section: Preclinical Studies Of Serotonergic Changes Associated With mentioning
confidence: 99%